UPAYA GURU MENUMBUHKAN MINAT MENGENAL HURUF HIJAIYAH MELALUI METODE IQRO PADA ANAK USIA 5-6 TAHUN DI TK NEGERI 1 PEMBINA PAGARALAM - Elsi Agustina; Evi SN; Masrifa H (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze teachers' efforts in fostering interest in recognizing hijaiyah letters through the Iqro method among children aged 5–6 years at TK Negeri 1 Pembina Pagaralam. This research employed a qualitative approach with data collection techniques including interviews, observations, and documentation. The research subject was the Iqro teacher, while 40 students were observed using an assessment instrument consisting of 30 indicators. The results indicate that the implementation of the Iqro learning method, viewed from input, process, and output aspects, falls into the good to very good category. The input aspect is reflected in the readiness of learning objectives, curriculum, and adequate facilities. The process aspect shows interactive, gradual, and enjoyable learning through repetition methods, two-way communication, and positive feedback. The output aspect reveals that 71% of students achieved good to very good levels in learning objectives, and 74% demonstrated significant competency improvement. However, the study also found that learning success is not solely influenced by school factors but is also affected by family support and individual differences among children. Therefore, the Iqro method is proven effective in fostering interest and ability in recognizing hijaiyah letters in early childhood, with the need for synergy between schools and families to achieve optimal results.